Micro-MRI at 11.7 T of a Murine Brain Tumor Model Using Delayed Contrast Enhancement - Rex A. Moats; Sendhil Velan-Mullan; Russell Jacobs; Ignacio Gonzalez-Gomez; David J. Dubowitz; Takashi Taga; Vazgen Khankaldyyan; Linda Schultz; Scott Fraser; Marvin D. Nelson; Walter E. Laug (Molecular Imaging)
In vivo imaging methodologies allow for serial measurement of tumor size, circumventing the need for sacrificing mice at given time points. In orthotopically transplanted murine models of brain tumors, cross-section micro-MRI allows for visualization and measurement of the physically inaccessible tumors. To allow for long resident times of a contrast agent in the tumor, intraperitoneal administration was used as a route of injection for contrast-enhanced micro-MRI, and a simple method for relative tumor volume measurements was examined. A strategy for visualizing the variability of the delayed tumor enhancement was developed. These strategies were applied to monitor the growth of brain tumors xenotransplanted into nude mice and either treated with the antiangiogenic peptide EMD 121974 or an inactive control peptide. Each mouse was used as its own control. Serial imaging was done weekly, beginning at Day 7 after tumor cell implantation and continued for 7 weeks. Images obtained were reconstructed on the MRI instrument. The image files were transferred off line to be postprocessed to assess tumor growth (volume) and variability in enhancement (three-dimensional [3-D] intensity models). In a small study, tumor growth and response to treatment were followed using this methodology and the high-resolution images displayed in 3-D allowed for straightforward qualitative assessment of variable enhancement related to vascular factors and tumor age.